Dynamic sealing simulation and performance optimization of conical rubber core in rotary blowout preventer - Lianglin Guo; Zhiqiang Huang; Hao Huang; Hao Zhang; Fubin Xin; Junjie Ji; Chengyu Xia; Hengda Che (Scientific Reports)
Abstract During the underbalanced pressure drilling, the conical rubber core of the rotary blowout preventer((RBOP) is susceptible to alternating cyclic stress due to the alternating passage of the drill pipe body and its joint, which can easily lead to fatigue cracking and sealing failure. To improve the performance of the rubber core, the constitutive parameters of the rubber were obtained by fitting the uniaxial tension and compression test results with the Yeoh constitutive model. Subsequently, the finite element model of the dynamic sealing was established to simulate the sealing and stress law of the contact surface between the rubber core and the drill pipe. It can be concluded that the inner cylindrical surface of the rubber core is the main force bearing surface compared to other parts. The stress value is highest during the transition period when the drill pipe joint alternates with the drill pipe body. The stress amplitude of the sealing surface under the initial structure is 5.14 MPa, and the peak stress is 22.98 MPa. Then, Plackett-Burman (PB) design was used to screen out three structural parameters, which had significant effects on the sealing surface. Sensitivity analysis was conducted on significant factors to determine their effects on sealing stress. Combined with response surface design, the optimal combination of structural parameters was cone angle 27.7°, contraction angle 68.2°and inner diameter 82.1 mm. After optimization, the peak value of Mises stress was reduced by 3.64 MPa, the amplitude of Mises stress was reduced by 39%, and the prediction error was only 0.42 MPa, which verified the validity and accuracy of the response surface prediction model. This research can help effectively prolong the service life of the rubber core and reduce the risk of wellhead blowout.